2021
DOI: 10.2486/indhealth.2021-0069
|View full text |Cite
|
Sign up to set email alerts
|

Association between working overtime and psychological stress reactions in elementary and junior high school teachers in Japan: a large-scale cross-sectional study

Abstract: This study aimed to investigate the relationship between working overtime and psychological stress reactions among school teachers. It also evaluated the interaction of overtime work types (on weekdays, on holidays, and bringing work home) and task content (educational, peripheral and both). This cross-sectional study was conducted on Japanese elementary and junior high school teachers. Primary outcome was psychological stress reactions measured with the Brief Job Stress Questionnaire. Participants were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…These events included school trips, class visitations by parents, sports events, demonstration lessons involving attendance from other schools, and other extracurricular activities. The tasks related to these activities place a considerable workload on teachers in Japan 18) . These activities will contribute greatly to the growth and development of students and are likely to be of great significance in their lives.…”
Section: Discussionmentioning
confidence: 99%
“…These events included school trips, class visitations by parents, sports events, demonstration lessons involving attendance from other schools, and other extracurricular activities. The tasks related to these activities place a considerable workload on teachers in Japan 18) . These activities will contribute greatly to the growth and development of students and are likely to be of great significance in their lives.…”
Section: Discussionmentioning
confidence: 99%
“…The main factors contributing to overtime for 9-1-1 telecommunicators are understaffing and low retention rates (Moore, 2019). Previous studies described the mechanism of understaffing, overtime, and stress (Furihata et al, 2022;Northwest Center for Public Health Practice, n.d.;Stimpfel et al, 2022). More work hours increase stress and burnout and discourage recruits, leading to a staff shortage.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding workload of clerical tasks, a relatively high percentage of teachers chose this as a main stressor, however, the association with stress response scores was practically significant only among vice-principals and diet and nutrition teachers. Previous studies indicated that paper-work associated with teaching and other peripheral tasks were significantly stressful for teachers (69,70). Clerical work, such as document preparation and other related duties, constitute approximately 5.6 h per week in Japan, more than double the average for all surveyed countries (20).…”
Section: Tenured Teacher Fixed-term Teachermentioning
confidence: 98%